MATH SOLVE

3 months ago

Q:
# 12) -7x + y=-19-2x + 3y =-19Solve by elimination

Accepted Solution

A:

X = 2Y = -5Step-by-step explanation:We will multiply -7x + y=-19 by 3 so we can make the ys identical with the second equation. This way, its easier to eliminate them;3(-7x + y=-19) =-21x + 3y = -57Then we can eliminate the ys by elimination. Be keen with the sign before each value;-21x + 3y = -57--2x + 3y =-19=-19x = - 38X = -38 / -19X = 2We can substitute the value of x in one equation get the value of y;-7(2) + y = -19-14 + y = -19Y = -19 +14Y = -5Learn More:For more on solving equations by elimination check out;